Jo Holley: capstone - Holley, Jo, artist (Colorado State University. Libraries, 2026)
The artist's statement: NOM is a branding project built around frozen, ready to heat meals that would be free for students and available to help fight food insecurity. The brand features bold colors and friendly patterns that would be inviting to potential participants in the program. NOM is inspired by the playful sounds of eating yummy food and also stands for "nourish our minds". This food is made thoughtfully with love and care to be nutritious brain fuel for hungry students. I wanted the branding to feel exciting and inviting so users would feel happy about the choice they're making to pick up a meal. The eye-catching colors pull you in and the recurring motifs add to the fun!
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: graphic design